Metode Pengembangan Kecerdasan Sosial dalam Pembelajaran Al-Qur’an Hadits di Pondok Pesantren Yatim An-Nursali Binjai Sumatera Utara - Arlina Arlina; Zulkipli Nasution; Azhar Mansyur Nasution; Maisarah Maisarah (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Methods for Developing Social Intelligence in Learning Al-Qur'an and Hadith at An-Nursali Binjai Islamic Boarding School, North SumatraSocial intelligence is a good potential in children and is the main capital to gain success in life. The importance of social intelligence for children is the focus of this research, so this study aims to find the methods used by teachers to develop social intelligence in learning Al-Qur'an and Hadith, and explain the reasons teachers use these methods. This study uses a phenomenological qualitative method which aims to analyze the phenomenon and its context. The phenomenon analyzed is the development of social intelligence in learning Al-Qur'an Hadith at An-Nursali Binjai Islamic Boarding School which consists of developing learning inside and outside the classroom. The social intelligence of students is developed through exemplary methods, habituation, punishment, giving advice for students who violate the rules, and halaqah activities. According to the teacher, the use of this method gives students the opportunity to dig up information and ask questions related to the subject matter. In addition, the material discussed is not only memorizing verses of the Qur'an and performing worship (hablumminallah) but also discussing muamalah (hablumminannas), so that students' social intelligence can be fostered cognitively, affectively and psychomotorically based on Allah's commands in the Qur'an